2016
DOI: 10.1017/s1755048315000814
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Culture, Oil, and Women's Rights Revisited

Abstract: According to recent research, oil abundance is the principal explanation for women's poor human rights record in many Muslim societies. However, this study argues that resistance to gender equality in the Muslim world originates in its specific historical trajectory and that the critical juncture precedes the extraction of oil by a thousand years. The study assesses data on women's economic, social, and political rights in 166 countries from 1999–2008 and shows that whereas the negative effect of oil is driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Należy tu zwrócić uwagę na rolę kobiet podyktowaną uwarunkowaniami kulturowymi, w których żyją muzułmanki. Trzonem kultury islamskiej jest bowiem ortodoksyjny patriarchat, w związku z czym pozycja kobiet jest w niej uzależniona od mężczyzn i ulega znacznym ograniczeniom zwłaszcza w sferze seksualności 64 . Stosowana przemoc seksualna nie tylko powodowała więc faktyczne obrażenia, lecz także narażała ofiary na ostracyzm społeczny, przemoc ze strony krewnych, a nawet męża 65 .…”
Section: Sprawa Kadic V Karadžićunclassified
“…Należy tu zwrócić uwagę na rolę kobiet podyktowaną uwarunkowaniami kulturowymi, w których żyją muzułmanki. Trzonem kultury islamskiej jest bowiem ortodoksyjny patriarchat, w związku z czym pozycja kobiet jest w niej uzależniona od mężczyzn i ulega znacznym ograniczeniom zwłaszcza w sferze seksualności 64 . Stosowana przemoc seksualna nie tylko powodowała więc faktyczne obrażenia, lecz także narażała ofiary na ostracyzm społeczny, przemoc ze strony krewnych, a nawet męża 65 .…”
Section: Sprawa Kadic V Karadžićunclassified
“…From among these explanations, structural socioeconomic conditions, related to the notions of power, status, and prestige in society, present themselves as a dominant explanatory variable for the persisting gender gap, particularly in the Western societies (Inglehart & Norris, 2003). On the other hand, from the value‐systems cultural perspective, previous accounts observed that gender gaps are uniquely endemic to the Muslim‐majority countries, implying a negative association between Islam and Muslim women's political rights and participation (Fish, 2002; Norris & Inglehart, 2011; Rorbæk, 2015). However, more recent cross‐national empirical studies have found no direct evidence to substantiate the link between Islam and the gender gap with respect to political activism (Achilov, 2016; Coffé & Dilli, 2015).…”
Section: Gender Gap and Political Mobilizationmentioning
confidence: 99%
“…Even though Muslim-majority states exhibit disproportionately higher occurrences of civil wars, the early stages of the Arab Spring, the Green Movement in Iran, as well as two successful Tulip revolutions in Kyrgyzstan are just some examples of anti-authoritarian nonviolent protests that have been taking place in the predominantly Muslim countries. Progressive and democratic elements of such demonstrations are significant, yet Muslim polities and cultures are generally noted for large gender gaps in many spheres of public life, including low level of empowerment and limited rights for women (Fish, 2002;Rorbaek, 2015). Consequently, it is unsettling that women, who are already disadvantaged in many areas, are also underrepresented in the collective protest events that take place in the Arab (and, generally, Muslim) street.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable body of literature focuses on the latter cause and shows that the real culprit for the lack of democratic institutions in the Middle East is Islam and its deep institutional factors that historically precede the importance of oil (Fish 2002, 2011; Kuran 2016; Lust 2011; Norris 2013). In fact, several studies point out that oil rich Islamic countries were largely autocratic long before the discovery of oil (Chaney 2012; Kuran 2013; Rørbæk 2016). While some have argued that Islam has many resources to accommodate a successful democratic state (Esposito and Voll 1996; Salame 1994), other studies argue that Islam is inherently incompatible with democracy, judging from the (usual) low scores of democracy recorded by Muslim-majority countries (Fukuyama 1992; Huntington 1996; Lewis 1993; Zakaria 2004, 4) claims, “certainly the Koranic model of leadership is authoritarian.”…”
Section: Introductionmentioning
confidence: 99%